A Minimal Violence: Seven Theses on the Classical Style - Waltham-Smith, Naomi (Les Cahiers de la Société québécoise de recherche en musique, 2010)
This article proposes a series of speculative and likely controversial theses about the ethical possibilities and dangers of the Classical style. Taking a concept of ethics that is both Heideggerian and subtractive in the mode of recent French thought, it begins by arguing that music itself—in its structures and stylistic features and not merely in the contingent circumstances of its genesis or reception—is capable of being an ethics. The next crucial claim is that, insofar as ethics is a question of proximity to one’s Being, the Classical style is minimally violent in Derrida’s sense both on account of the place it occupies in the emergence of an aesthetic disposition and, moreover, insofar as its construction hinges on a process of articulation, that is on the separation of form and content, of convention and expression. Finally, the article assesses how the Classical style responds to the fundamental principle of division at its heart.